2008
DOI: 10.1007/s11356-008-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and temporal variations of the xenoestrogens bisphenol A, 4-tert-octylphenol, and tech. 4-nonylphenol in two German wastewater treatment plants

Abstract: Further research is needed to investigate whether the observed decrease of tech. 4-nonylphenol concentrations in German WWTPs since June 2004 will continue further on. The reason for the high effluent concentrations of bisphenol A in only a few samples has to be clarified in further research. The results from this study provide insight into the concentration development of the xenoestrogens bisphenol A, tech. 4-nonylphenol, and 4-tert-octylphenol in WWTPs in the time span between 2003 and 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Many studies suggest that these chemicals preferentially enter into the environment through urban sources (Sharma et al 2009;Ying et al 2002). Among the urban sources investigated in the literature, the effluents of wastewater treatment plants (WWTP) are frequently studied (Hohne and Puttmann 2008;Loyo-Rosales et al 2007;Voutsa et al 2006;Zhou et al 2010). On the contrary, studies on wet weather urban sources such as combined sewer overflows (CSOs) and urban runoff are less available, despite their high contamination (Björklund et al 2009;Gasperi et al 2008).…”
Section: )mentioning
confidence: 99%
“…Many studies suggest that these chemicals preferentially enter into the environment through urban sources (Sharma et al 2009;Ying et al 2002). Among the urban sources investigated in the literature, the effluents of wastewater treatment plants (WWTP) are frequently studied (Hohne and Puttmann 2008;Loyo-Rosales et al 2007;Voutsa et al 2006;Zhou et al 2010). On the contrary, studies on wet weather urban sources such as combined sewer overflows (CSOs) and urban runoff are less available, despite their high contamination (Björklund et al 2009;Gasperi et al 2008).…”
Section: )mentioning
confidence: 99%
“…For quantification of the technical mixture of 4-nonylphenol isomers, the method previously described by Fries and Püttmann (2003b) and Höhne and Püttmann (2008) was applied. TCEP was analyzed using the method described by Quednow and Püttmann (2008b) and terbutryn was analyzed according to Quednow and Püttmann (2007).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…EDCs include certain types of pesticides, plasticizers, and other industry-related materials as well as natural compounds such as human hormones and their breakdown products (Arditsoglou and Voutsa 2008;Sibel et al 2005). Extensive studies carried out recently in the Netherlands, Germany, and other European countries showed that almost all selected (xeno-)estrogens are present at higher or lower concentrations in the aquatic environment (Johnson et al 2005) and effluent discharged into rivers carry an estrogenic potential (Höhne and Püttmann 2008;Keiter et al 2006).…”
mentioning
confidence: 99%